Childhood obesity and school absenteeism: a systematic review and meta‐analysis. (18th September 2017) - An, R.; Yan, H.; Shi, X.; Yang, Y.
Summary: Regular school attendance is a key determinant of student's academic achievement and psychosocial development. Obesity may affect children's school attendance through its detrimental impact on their physical and mental health. A literature search was conducted in the PubMed, Web of Science and Cochrane Library for articles published until April 2017 that examined the relationship between unhealthy body weight and school absenteeism among children and adolescents. Thirteen studies total (10 cross‐sectional and three longitudinal) conducted in seven countries were identified. The mean and median sample sizes were 24, 861 and 3, 113, respectively. Ten studies objectively measured children's height and weight, and three were based on parents' self‐report. Four studies measured absenteeism using school administrative data, and nine administered questionnaires on children's parents. Among them, 11 reported a statistically significant positive association between childhood overweight/obesity and school absence, whereas two reported null effect. The meta‐analysis found that the odds of being absent from school was 27% and 54% higher among children with overweight and obesity than among their normal weight counterparts, respectively. Future studies should adopt an experimental study design and accurate measures on school attendance and delineate the underlining pathways linking childhood obesity to school absenteeism through obesity‐related illnesses and psychosocial problems.